2012
DOI: 10.1100/2012/408949
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Performance between Surface Fitting and Energy Distribution in Turbulence Runner

Abstract: Because the application of surface fitting algorithms exerts a considerable fuzzy influence on the mathematical features of kinetic energy distribution, their relation mechanism in different external conditional parameters must be quantitatively analyzed. Through determining the kinetic energy value of each selected representative position coordinate point by calculating kinetic energy parameters, several typical algorithms of complicated surface fitting are applied for constructing microkinetic energy distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Based on the obtained index of T C (i ), it demonstrates the predicted characteristics in the portioned universe ranged from 0 to 8, thereafter the turbulence characteristics can be transferred into the predicted value (Liang, Liu, & Ye, 2012): Value Range 160-590 290-600 200-500 300-600 100-400 Value Range 100-550 100-300 100-500 200-700 100-500…”
Section: Fuzzy Predictionmentioning
confidence: 99%
“…Based on the obtained index of T C (i ), it demonstrates the predicted characteristics in the portioned universe ranged from 0 to 8, thereafter the turbulence characteristics can be transferred into the predicted value (Liang, Liu, & Ye, 2012): Value Range 160-590 290-600 200-500 300-600 100-400 Value Range 100-550 100-300 100-500 200-700 100-500…”
Section: Fuzzy Predictionmentioning
confidence: 99%
“…Stainless steel material was employed to manufacture the experimental platform, with the purpose of avoiding the high light reflective index and mirror effect of background material, causing these two physical phenomena to reduce the contrast ratio and blur the objective clearance in video image remarkably [ 38 , 39 ]. On the stainless steel pathways, the drug tablets were scattered into the monitoring field for high-speed video detection.…”
Section: Experiments For Drug Tablet Trackingmentioning
confidence: 99%
“…Simultaneously, Hellín et al [8] and Opan et al [9] respectively reported their instructive studies of irrigation effctiveness improvement using the DPSA-based (Dynamic Programming Successive Approximation) optimization model. More studies concerning the irrigation effectiveness schedule, and the effect of subsurface drip irrigation compared with that of surface drip irrigation, can be summarized from literature [10,11] accordingly. Relevant researches focusing on the upgrading of supplemental irrigation effectiveness for wheat production are published in literature [12] , either.…”
Section: Introductionmentioning
confidence: 99%